Impact of Climate Change on the Characteristics of Indian Summer Monsoon Onset. (15th September 2014) - Patwardhan, Savita; Kulkarni, Ashwini; Krishna Kumar, K.
Abstract : A high resolution regional climate modeling system, known as PRECIS (Providing REgional Climate for Impact Studies), developed by Hadley Centre for Climate Prediction and Research, UK, is applied for Indian subcontinent to assess the impact of climate change on the summer monsoon onset characteristics. The present day simulation (1961–1990) with PRECIS is evaluated for the characteristics of onset over Kerala, southernmost part of India, where the monsoon sets in over Indian landmass. The meteorological parameters like precipitation, outgoing long wave radiation (OLR), and low level winds are analysed to study the monsoon onset over Kerala. The model is able to capture the sudden and sharp increase of rainfall associated with the onset. The rapid built-up of convective activity over the southeastern Arabian Sea and Bay of Bengal is well represented by the model. PRECIS simulations, under scenarios of increasing greenhouse gas concentrations and sulphate aerosols, are analysed to study the likely changes in the onset characteristics in future, towards the end of present century (2071–2100). The analysis does not indicate significant difference in the mean onset dates in A2 and B2 scenarios. However, the variability of onset date is likely to be more towards the end of the 21st century especially in A2 scenario.